Happiness Becomes You: A Guide to Changing Your Life for Good - Tina Turner (Great Britain Atria Books, 2020)
Tina is a global icon of hope. And now, with Happiness Becomes You, she shows how anyone can overcome obstacles in life--even transform the impossible to possible--and fulfill our dreams. She shows how we, too, can improve our lives, empowering us with spiritual tools and sage advice to enrich our unique paths. For decades, Tina has shined brightly as an example of someone who can generate hope from nothing, break through all limitations, and achieve success that endures. Drawing on the lessons of her own experiences--rising out of sorrowful lows to stratospheric heights--she illuminates the practical principles of Buddhism and how they have helped her elevate from despair, adversity, and poverty to joy, stability, and prosperity. Now, Tina offers the wisdom of an extraordinary lifetime in Happiness Becomes You making this the perfect gift of inspiration for you and those you love.
Keywords: Autobiography; Nonfiction; Spirituality; Self Help